2015
DOI: 10.1126/scitranslmed.aaa2293
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection enhances the immune response to influenza

Abstract: Cytomegalovirus (CMV) is a beta-herpes virus present in a latent form in most people worldwide. In immunosuppressed individuals, CMV can reactivate and cause serious clinical complications, but the effect of the latent state on healthy people remains elusive. We undertook a systems approach to understand the differences between seropositive and negative subjects and measured hundreds of immune system components from blood samples including cytokines and chemokines, immune cell phenotyping, gene expression, ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
297
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(328 citation statements)
references
References 77 publications
20
297
2
1
Order By: Relevance
“…This finding suggests that CMV infection may enhance the activation process of memory B cells in both young and elderly participants. Age-related deficiencies of other immune components or a lessened ability to diversify the existing memory pool into high-affinity antibodies in aging may explain why an enhanced serum antibody response to influenza vaccine has been detected only in young, but not in elderly, CMV + individuals (36).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that CMV infection may enhance the activation process of memory B cells in both young and elderly participants. Age-related deficiencies of other immune components or a lessened ability to diversify the existing memory pool into high-affinity antibodies in aging may explain why an enhanced serum antibody response to influenza vaccine has been detected only in young, but not in elderly, CMV + individuals (36).…”
Section: Resultsmentioning
confidence: 99%
“…Results on the effect of CMV seropositivity on influenza vaccine responses are controversial with most of the studies showing a negative effect of CMV (Derhovanessian et al 2013b(Derhovanessian et al , 2014Frasca et al 2015;Trzonkowski et al 2003) and others showing no effect (den Elzen et al 2011;Furman et al 2015). The negative effects of CMV seropositivity have been associated in both elderly (Derhovanessian et al 2013b;Frasca et al 2015) and young (Frasca et al 2015) individuals with the presence of late differentiated/exhausted T cells (CD27 −CD28−CCR7−CD45RA+ or with CD28−CD57+), which produce pro-inflammatory cytokines and have therefore a significant role in age-related immune pathologies, suggesting that this virus may underlie rudimentary aspects of immunosenescence even in chronologically young individuals (Turner et al 2014).…”
Section: Infectious Diseases and Vaccine Responsesmentioning
confidence: 99%
“…Results from a recently published study have demonstrated that CMV seropositivity negatively affects antibody response to the influenza vaccine to a greater extent than inflammatory markers, such as β2-microglobulin and IL-6, in older adults (Reed et al 2017). Conversely, the positive effects of CMV seropositivity on the response to the influenza vaccine have been shown only in young individuals (Furman et al 2015). In particular, it has been shown that CMV-seropositive young individuals exhibited enhanced in vivo antibody responses, Th1 and Th2 responses, and cytotoxic T cell responses, as compared with CMV-seronegative individuals, suggesting that CMV can boost the immune response of young individuals and therefore shows features of a mutualistic agent conferring benefits to the host.…”
Section: Infectious Diseases and Vaccine Responsesmentioning
confidence: 99%
“…In the elderly, chronic latent HCMV infection increases the mortality rate, which could be attributed to HCMV-induced immunosenescence with decreased immunity to microbes and cancers (Pawelec et al, 2010;Sansoni et al, 2014;Savva et al, 2013). In the non-elderly, on the other hand, chronic HCMV infection may actually be beneficial in that it augments the T-cell immunity and has been associated with a reduced cancer risk in transplant patients (Couzi et al, 2010;Furman et al, 2015;Pera et al, 2014). In this study, significant intra-tumoural inflammatory responses were more frequently observed in HCMVpositive tumours, suggesting that viral replication may activate the immune response in the tumour microenvironment and contribute to a favourable prognosis (Naito et al, 1998).…”
Section: Discussionmentioning
confidence: 99%